2022
DOI: 10.33417/tsh.981945
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Hizmet Bölümü Öğrencilerinin İş Bulma Endişeleri ve Umutsuzluk Düzeylerine Yönelik Bir Araştırma

Abstract: Bir amacı gerçekleştirmede sıfırdan az olan beklentiler olarak ifade edilen umutsuzluk sosyal hizmet öğrencileri ve öğrencilerin iş bulma endişeleri açısından irdelenmeye değer bir konudur. Yürütülen bu araştırmada sosyal hizmet bölümü öğrencilerinin iş bulma endişeleri ile umutsuzluk düzeylerini belirleyerek bunları çeşitli değişkenlere göre irdeleme ve bu doğrultuda var olan durumu daha iyi anlama amacı taşımaktadır. Nicel olarak tasarlanan çalışmaya 1592 sosyal hizmet bölümü öğrencisi katılmıştır. Araştırma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In particular, students living in the city centre had higher averages in the "locus of control" and "communication" sub-dimensions of the individual entrepreneurship perception scale. When the literature is examined, besides the existence of similar ndings (Korkmaz, 2012) 2021), it was concluded that students' expectations for the future were found to be low due to the decrease in employment in the social work department and that students of the social work department were concerned about nding a job after graduation (Çay & Akpınar, 2022). In our research, it was found that the hopelessness levels of the second year students were higher than the students in other grade levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, students living in the city centre had higher averages in the "locus of control" and "communication" sub-dimensions of the individual entrepreneurship perception scale. When the literature is examined, besides the existence of similar ndings (Korkmaz, 2012) 2021), it was concluded that students' expectations for the future were found to be low due to the decrease in employment in the social work department and that students of the social work department were concerned about nding a job after graduation (Çay & Akpınar, 2022). In our research, it was found that the hopelessness levels of the second year students were higher than the students in other grade levels.…”
Section: Discussionmentioning
confidence: 97%
“…In our research, it was found that the hopelessness levels of the second year students were higher than the students in other grade levels. In a study conducted in Turkey, the lowest level of hopelessness was found among rst-year students (Çay & Akpınar, 2022), while in another study, it was determined that students' hopelessness levels increased after the second year (Kaya Mutlu et al, 2017). The fact that the awareness of vocational career is low in the rst years of the university and the market related to the profession is not su ciently recognised can be considered as an effective factor in obtaining this result.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the increase in university graduates in our country, their professional and economic problems begin while they are still in school and only once they leave school and start the job hunt (Musayev & Akcan, 2022). Similarly, Çay and Akpınar (2022) concluded in their study that the employment opportunities and future expectations of people studying in the social services department significantly impacted feelings of despair. One other finding of the present study is that the participants are concerned about the future.…”
Section: Discussionmentioning
confidence: 99%